2008
DOI: 10.1002/ccd.21599
|View full text |Cite
|
Sign up to set email alerts
|

Lack of clinical long‐term benefit with the use of a drug eluting stent compared to use of a bare metal stent in saphenous vein grafts

Abstract: Background: Small randomized trials have shown short-term improved outcome with drug-eluting stents (DES) over bare metal stent (BMS) in saphenous vein graft (SVG) interventions by reducing in-stent restenosis and target vessel revascularization (TVR). It is not clear, however, if these benefits are maintained long term. The aim of this study is to compare the outcome in a larger cohort of patients undergoing SVG stent implantation with DES or BMS, at 2 years. Methods: From among 250 patients who underwent SVG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…However, there is a paucity of prospective data on DES in SVG interventions, although BMS is associated with high restenosis rates in SVG lesions. The results of mostly retrospective observational series comparing DES with BMS in SVGs have been conflicting: 6 studies showed better results with DES (9 -14) and 9 suggested no difference between BMS and DES (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 97%
“…However, there is a paucity of prospective data on DES in SVG interventions, although BMS is associated with high restenosis rates in SVG lesions. The results of mostly retrospective observational series comparing DES with BMS in SVGs have been conflicting: 6 studies showed better results with DES (9 -14) and 9 suggested no difference between BMS and DES (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 97%
“…The majority of trials compared both SES and paclitaxel-eluting stents (PES) with BMS. In 1 trial, 28 SES, PES, and tacrolimuseluting stents were compared with BMS. Zotarolimus-eluting stents were used in a minority of patients (8%) in 1 study.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Periprocedural treatment with clopidogrel was more disparate among eligible studies. In most trials, clopidogrel was prescribed for at least 1 month after BMS placement 13,[17][18][19][21][22][23]25,[27][28][29]36 and for at least 3 18 -20,22,25,28 or 6 months 13,14,17,19,21,23,25,27,28,32,33,36,37 after DES implantation. In the DELAYED RISCC study, 12 clopidogrel was administered for at least 2 months in all patients.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Two newer reports have continued the trend of presenting null or positive results. Gioia et al (5) reported that 106 patients treated with DES for SVG lesions had similar rates of event-free survival (81% vs. 82%, p ϭ 0.9), target vessel revascularization (14% vs. 14%, p ϭ 1.0), or death (6% vs. 6%, p ϭ 1.0) at 2 years, compared with 119 patients treated with bare-metal stents. Brodie et al (6) reported that 825 patients treated with DES for SVG lesions had lower rates of target vessel revascularization at 9 months than 361 patients with bare-metal stents (7.5% vs. 9.4%, p Ͻ 0.05).…”
Section: See Page 919mentioning
confidence: 88%